(untitled) (Revista Educação, Artes e Inclusão, 2025)
When discussing studies related to inclusive education, one understands the struggle experiencedby this social group in different historical moments: segregation, integration and inclusion of peoplewith disabilities (PWD) in social and educational spaces, and which policies and strategies areemployees recognizing their needs. Therefore, this article presents an analysis of inclusiveeducation policies and guidelines at the Federal Institute of Paraná (IFPR), focusing on the accessand retention of students with disabilities in secondary technical education. Based on a literaturereview and analysis of the institution’s normative documents, such as the Institutional DevelopmentPlan (PDI) 2019/2023, the Institutional Pedagogical Project (PPI) and the 2023 Selection Processnotice, the study investigates how the IFPR adopts inclusion, diversity and accessibility policies.The PDIreaffirms the institution’s commitment to valuing diversity, implementing actions such associal quotas and assistive technologies. The role of CONAPNE (Support Committee for Peoplewith Special Needs) is highlighted in the coordination of inclusive policies. Analysis of the SelectionProcess notice demonstrates that theIFPR guarantees accessibility and equal opportunities forpeople with disabilities, in line with current legislation. It is concluded that, although thedocumentary analysis does not cover all institutional practice, the IFPR demonstrates a clearcommitment to promoting inclusive education, valuing human differences and defending educationas a universal right.